PENGARUH BIAYA PENDIDIKAN DAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X DAN XI IIS PADA MATA PELAJARAN EKONOMI SMA NEGERI 2 XIII KOTO KAMPAR - Sonata, Utari; Sumarno, Sumarno; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : This study aims to determine the Influence of Education Costs and Learning Facilities Against Student Results Class X and XI IIS On Economic Subjects SMA Negeri 2 XIII Koto Kampar. The population in this study are students of class X and XI SMA Negeri 2 XIII Koto Kampar as much as 52. The study took the entire population as a sample or called census research. Data collection is done through documentation and questionnaire. Data analysis used multiple regression analysis. The results showed that the cost of personal education has no effect while the home study facilities affect the learning outcomes. This can be shown from the constant value (a) of 58.808 and the regression coefficient value X1 (b1X1) of 1.548E-7 and the regression coefficient X2 (b2X2) of 0,593 with regression equation 58,808 + 1,548E-7 X1 + 0,593 X2. Judging from the calculation of R2 (R Square Change) obtained value of 0.185. This means that the contribution of the cost of education and learning facilities on learning outcomes is 18.5%Keywords : Education Cost, Learning Facilities, Student achievement